Validation of single-plane fluoroscopy and 2D/3D shape-matching for quantifying shoulder complex kinematics. (February 2018) - Lawrence, Rebekah L.; Ellingson, Arin M.; Ludewig, Paula M.
Highlights: Validation of single-plane fluoroscopy and 2D/3D shape-matching is performed. The methodology can accurately quantify full shoulder complex kinematics. Kinematic errors should be fully described using anatomical descriptions. Abstract: Fluoroscopy and 2D/3D shape-matching has emerged as the standard for non-invasively quantifying kinematics. However, its accuracy has not been well established for the shoulder complex when using single-plane fluoroscopy. The purpose of this study was to determine the accuracy of single-plane fluoroscopy and 2D/3D shape-matching for quantifying full shoulder complex kinematics. Tantalum markers were implanted into the clavicle, humerus, and scapula of four cadaveric shoulders. Biplane radiographs were obtained with the shoulder in five humerothoracic elevation positions (arm at the side, 30°, 60°, 90°, maximum). Images from both systems were used to perform marker tracking, while only those images acquired with the primary fluoroscopy system were used to perform 2D/3D shape-matching. Kinematics errors due to shape-matching were calculated as the difference between marker tracking and 2D/3D shape-matching and expressed as root mean square (RMS) error, bias, and precision. Overall RMS errors for the glenohumeral joint ranged from 0.7 to 3.3° and 1.2 to 4.2 mm, while errors for the acromioclavicular joint ranged from 1.7 to 3.4°. Errors associated with shape-matching individual bones ranged from 1.2 to 3.2° for the humerus, 0.5 to 1.6° for the scapula, and 0.4 to 3.7° for the clavicle. The results of the study demonstrate that single-plane fluoroscopy and 2D/3D shape-matching can accurately quantify full shoulder complex kinematics in static positions.